(untitled) (Indian Journal of Experimental Biology (IJEB), 2025)
Sleep deprivation negatively impacts well-being including increased stress levels, reduced cognitive performance and weakened immune systems. Twenty five female Wistar rats weighing 150–200 g were split into five groups of five rats each. Group I served as the normal control, while Group II was the negative control (sleep-deprived untreated). Groups III, IV, and V were administered varying doses of the HS extract via gavage at 100, 200 and 400 mg/kg respectively. The animals were anaesthetized and sacrificed, and blood samples were collected for biochemical assessment. HS notably reduced oxidative stress (P< 0.05) by improving the activities of key enzymatic antioxidants, including SOD, GPx, and CAT, while lowering ROS production in comparison to the SD-untreated group. Additionally, HS treatment led to a significant increase (P< 0.05) in the levels of interleukin-10 (IL-10) and brain-derived neurotrophic factor (BDNF), alongside a marked decrease in TNF-alpha levels when compared to the SD-untreated groups. The study demonstrated that HS treatment significantly (P< 0.05) improved hematological indices. In conclusion, HS extract modulates oxidative stress and inflammation via its effect on key antioxidant enzymes; SOD, GPx and CAT, inflammatory biomarkers; IL-10 and TNF-alpha as well as BDNF. It also improves hematological indices in female sleep-deprived animals.